Evaluación presupuestaria al primer semestre del 2023 y planificación financiera año 2024 para el GAD Municipal de Portovelo. - Betancourt Landívar, Jaime Enrique (2024)
Budget evaluation and financial planning are fundamental tools in the economic management of resources, both in the private and public sectors. In a governmental sector company, a very important role is the management of resources in an efficient and effective way and for this it is transcendental to carry out evaluations to the finances of the entities periodically, reason for which the proposal of my thesis called: Budgetary evaluation to the first semester of 2023 and financial planning year 2024 for the Municipal Government of Portovelo arises. The methodology used was based on the deductive-analytical method with a mixed approach, to determine the incidence of the budget evaluation in financial planning, through the collection of information from the income and expenditure budget documents, and the results of the Annual Operational Plan of the entity. The research work determines the impact of evaluation on planning through Pearson's correlation model, identifying the trend line between the two variables. In this entity, the management of the budget for each period depends largely on the Ecuadorian State, which through the Ministry of Economy and Finance, issues in the General State Budget the allocation of resources for the Municipal GADs. Under this premise, the research proposal shows in the report the most critical areas or those that present risks for the institution, in order to address them and make the corresponding adjustments for the next fiscal period, concluding that it is of great importance the application of financial tools in government entities to measure their financial health, allowing them to optimize resources in the best way, in addition to highlighting the need to reduce financial dependence and increase institutional autonomy to obtain their own income.